A crucial role of the malate aspartate shuttle in metabolic reprogramming in TNF-induced SIRS - Nuyttens, Louise; Heyerick, Marah; Roes, Maxime; Moens, Elise; Van Dender, Céline; Wallaeys, Charlotte; Hochepied, Tino; Timmermans, Steven; Vandewalle, Jolien; Libert, Claude (Frontiers in Immunology, 2025)
Tumor necrosis factor (TNF) causes a lethal systemic inflammatory response syndrome (SIRS) which is characterized by significant metabolic alterations. Based on liver RNA sequencing, we found that TNF impairs the malate-aspartate shuttle (MAS), an essential redox shuttle that transfers reducing equivalents across the inner mitochondrial membrane thereby recycling cytosolic NAD+. This downregulation of MAS genes in TNF-induced SIRS likely results from loss of HNF4α function, which appears to be the key transcription factor involved. Using Slc25a13-/- mice lacking citrin – a crucial MAS component – we demonstrate that MAS dysfunction exacerbates TNF-induced metabolic dysregulations and lethality. Disruptive NAD+ regeneration leads to diminished mitochondrial β-oxidation, leading to elevated levels of circulating free fatty acids (FFAs) and to hepatic lipid accumulation. Simultaneously, MAS dysfunction promotes glycolysis coupled to lactate production and reduces lactate-mediated gluconeogenesis, culminating in severe hyperlactatemia that triggers VEGF-induced vascular leakage. Overall, MAS dysfunction contributes to metabolic failure and lethality in TNF-induced SIRS, highlighting its potential as a promising, therapeutic target.